Who was that? (Chronicle Books LLC, 2018)
This fresh, visually sophisticated follow-up to Who Done It? and Who What Where? tackles the topic of memory, as each page asks the reader to remember a detail about the characters featured on the page before. With die-cuts, clever folds, and imaginative illustrations, this book requires the sharpest readers' keen attention! The call to action on every page makes this a wonderful lap read or read-aloud, and kids of all ages will love the memory games.

The memory of an elephant: an unforgettable journey (Chronicle Books, 2014)
Memory and meaning are at the heart of this oversized, content-rich picture book celebrating the life of Marcel, a soulful elephant. From the towering buildings outside his window and his recollected world travels, to the friends, flora, and fauna that flourish around him, Marcel finds significance in his surroundings and, most importantly, in life's abundant details. Marcel is writing an encyclopedia, after all, and his entries are featured in full-page spreads packed with facts, elegantly situated alongside the story of his day and his life. Part story and part miscellany, this unforgettable book with dream-like illustrations will transfix both parents and children.

Mamá ya viene (Takatuka, 2015)
Lisa's mother is so forgetful and distracted that the little girl fears that one day she won't remember to pick her up from school. Her mother reassures her that Lisa is something she would never forget.